2021
DOI: 10.1111/dme.14737
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic review of interventions to prevent inpatient hypoglycaemia

Abstract: Aims: This pragmatic review aimed to map and summarize the literature on model of care interventions to prevent inpatient hypoglycaemia. Model of care interventions were broadly defined as interventions that either directly target the workforce or where implementation had a strong workforce effect. The review intended to provide information for decision-makers in local health care settings regarding potential interventions to prevent inpatient hypoglycaemia in their local context. Methods: PubMed, Embase, CINA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Pragmatic literature review of intervention options A pragmatic literature review was undertaken that identified fortynine publications for forty-seven studies. Full details of the review are available as a published paper (6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pragmatic literature review of intervention options A pragmatic literature review was undertaken that identified fortynine publications for forty-seven studies. Full details of the review are available as a published paper (6).…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that “the time and cost required to conduct and interpret economic evaluations, and lack of expertise to evaluate quality and interpret results” have also been identified as barriers to the use of economic evaluation (23). However, transferable tools and materials were developed, including the clinical audit tool, the pragmatic literature review (6), the elicitation framework (15), and code for data analysis and economic modeling. Options for the dissemination of these resources include a consultancy model or training courses with resources developed to upskill local personnel to apply the evaluation tools and materials locally.…”
Section: Discussionmentioning
confidence: 99%
“…Health service delivery models are used to organize the effective delivery of health care. Based on a pragmatic literature review of potential delivery model intervention options 6 and a preliminary assessment of expected costs and benefits, the working group selected 2 interventions to be included in the final local-level economic analysis:…”
Section: The Broader Project: Local-level Economic Evaluation Overviewmentioning
confidence: 99%
“…While risk factors for inpatient hypoglycaemia are well known, some of them evolve dynamically during the patient stay, which limits the effectiveness of a single risk assessment on admission. In addition, evidence supporting interventions to reduce inpatient hypoglycaemia is limited, with education interventions, audit and feedback shown to be ineffective, for the most part, at reducing inpatient hypoglycaemia [4]. Conversely, published evidence supports the use of predictive-informatics risk-alert systems.…”
Section: Introductionmentioning
confidence: 99%